KEBIJAKAN FORMULASI TERHADAP ANAK SEBAGAI RESIDIVIS DALAM PEMBAHARUAN SISTEM PERADILAN PIDANA ANAK DI INDONESIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Crimes are not only committed by adults against children, but there are also crimes committed by children. The problem faced at this time is the number of juvenile delinquency cases with perpetrators are former convicted child convicts. The problem of repeated criminal acts (Recidivises) that occur against children in Indonesia is a complex problem and needs to be addressed immediately, so as not to cause unrest in the community. However, in the implementation of children as recidivists do not get clear arrangements in the juvenile justice system law.This type of research can be classified in normative legal research, namely legal research conducted by examining library materials. This study examines the subject matter in accordance with the scope and identification of problems through the statute approach carried out by examining the laws and regulations relating to the legal issues under study. In this study the authors conducted a study of legal principles by utilizing descriptive methods. Data collection techniques used in Normative Legal Research is a method of library research that uses the library as a means of collecting data, by studying books as reference material related to the problem to be examined.The conclusion that can be obtained from the results of the study is the Criminalization of children as a recidivist in the Child Criminal Justice System at this time there is still no regulation governing criminal sanctions against children who commit repetition of a crime (residive), both contained in the Criminal Code or in the Law Criminal Justice System for Children. The absence of basic considerations in the conviction of children both criminal incriminating and mitigating, especially against children as recidivists. The idea of criminalization of children as a recidivist in the renewal of the juvenile justice system in Indonesia is urgently needed in order to formulate a better Indonesian criminal law policy in the future. The idea expected by the author of efforts to cope with children as recidivists is one of them by prevention. Judges in this case must be able to provide a basis for consideration in convicting children both criminal incriminating or mitigating, especially against children as recidivists.Keywords: Policy Formulation, Children, Recidivist Reform, Child Criminal Justice System